2021
DOI: 10.1111/clr.13861
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s perception of timing concepts in implant dentistry: A systematic review

Abstract: Protocols for implant dentistry, most frequently include periods until healing of the extraction sockets and osseointegration of the implant. Deductional thinking imply that patients would prefer if treatment time in implant dentistry were reduced. Aim What is the patient perception of immediate or early implant placement or loading in comparison with traditional, delayed placement, and/or loading assessed by patient‐reported outcome measures, as evidenced in randomized controlled clinical trials or prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…According to the results of this pilot study, we plan an RCT with 20 patients for each group. There is a highly limited number of RCTs with PROMs as primary outcome [ 12 ] especially for single tooth reconstructions. Some of the recommendations of the EAO consensus statement [ 13 ] investigating PROMs of timing concepts in implant dentistry will be assessed in the upcoming RCT.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this pilot study, we plan an RCT with 20 patients for each group. There is a highly limited number of RCTs with PROMs as primary outcome [ 12 ] especially for single tooth reconstructions. Some of the recommendations of the EAO consensus statement [ 13 ] investigating PROMs of timing concepts in implant dentistry will be assessed in the upcoming RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review by Wittneben et al 42 examined patient-reported outcome measures focusing on the esthetics of implant-supported fixed dental prostheses and found corresponding results. They included 16 studies and only 3 of the included studies used PROMs as an equated outcome variable [43][44][45] Thus, although a number of international consensus reports and systematic reviews recommend including PROMs 19,46,47 this is seldom done as a primary outcome variable. Furthermore, studies including PROMs are missing concerning important questions about whether GBR should be performed staged or simultaneously with implant treatment.…”
Section: Proms In Other Bone Reg Ener Ati On S Tud Ie Smentioning
confidence: 99%
“…However, the appropriateness of the OHIP questionnaires for surgeries such as GBR or single tooth implants in young patients can be questioned. 18,19 Thus, the OHIP questionnaire was developed in the early 90s based on 535 statements from 64 selected patients of which 55% were wearing dentures and reliability was evaluated in a cohort of 122 patients aged 60 and older. Thus, the OHIP questionnaire may be applicable for older patients missing a great number of teeth, but for young patients with a high number of remaining teeth the appropriateness, acceptability, and interpretability are dubious.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no clarity if there is robust evidence supporting this assumption. In the present systematic review (Gotfredsen et al, 2021), the search strategy initially resulted in 1439 publications, but only 35 studies fulfilled the inclusion criteria and were eligible to be included in the descriptive analyses to answer the following questions set by the working group 1 during the Consensus Conference.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%